2021
DOI: 10.3390/ijms22052251
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Boronophenylalanine-Loaded Biodegradable Periodic Mesoporous Organosilica Nanoparticles for BNCT Cancer Therapy

Abstract: Biodegradable periodic mesoporous organosilica (BPMO) has recently emerged as a promising type of mesoporous silica-based nanoparticle for biomedical applications. Like mesoporous silica nanoparticles (MSN), BPMO possesses a large surface area where various compounds can be attached. In this work, we attached boronophenylalanine (10BPA) to the surface and explored the potential of this nanomaterial for delivering boron-10 for use in boron neutron capture therapy (BNCT). This cancer therapy is based on the prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 29 publications
(66 reference statements)
0
33
0
Order By: Relevance
“…BNCT involves irradiation of boron-10 with thermal neutrons to produce highly energetic α-particles that cause irreparable injuries in the DNA. Adapted with permission from [68]. Copyright MDPI, 2021.…”
Section: Towards Biodegradability Of Msns: Redox-responsive Bridged Npsmentioning
confidence: 99%
See 2 more Smart Citations
“…BNCT involves irradiation of boron-10 with thermal neutrons to produce highly energetic α-particles that cause irreparable injuries in the DNA. Adapted with permission from [68]. Copyright MDPI, 2021.…”
Section: Towards Biodegradability Of Msns: Redox-responsive Bridged Npsmentioning
confidence: 99%
“…Tamanoi et al recently reported an innovative approach for the treatment of tumors using biodegradable, bridged mesoporous silica NPs for boron neutron capture therapy (BNCT) ( Figure 12 ) [ 68 ]. BNCT involves irradiation of boron-10 with thermal neutrons to produce highly energetic α-particles that cause irreparable injuries in the DNA.…”
Section: Towards Biodegradability Of Msns: Redox-responsive Bridged Npsmentioning
confidence: 99%
See 1 more Smart Citation
“…This thematic area is associated with articles [ 12 , 15 , 20 , 21 , 26 , 50 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 ], of which there are a total of 50. In contrast to the areas already discussed above, articles of all four types are presented here ( Table 5 ), although, here, too, the Original constitutes a clear majority over the other 3 types of articles.…”
Section: Articles On the Various Directionsmentioning
confidence: 99%
“…Therefore, to take full advantage of the potential of stimuli-responsive polymers, these have been grafted to the surface of more robust nanocarriers [ 6 , 7 , 8 ]. Periodically ordered mesoporous silica materials, developed at Mobil by using surfactant micelles to template the condensation of reactive silica precursors [ 36 ], have been downsized to create mesoporous silica nanoparticles (MSNs), which are used as nanoscale carriers, in particular in drug delivery applications [ 37 , 38 , 39 ]. MSNs offer numerous design advantages for the development of smart nanocarriers, including high mechanical stability, well-defined particle morphology, tunable particle diameter (from 15 nm to several hundred nanometers) [ 40 ], tunable pore size (2–8 nm in diameter) and pore geometry (ordered/worm-like), and good colloidal stability [ 40 , 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%